Letters to His Friends - Robinson, Forbes, 1867-1904; Robinson, Charles H. (Charles Henry), 1861-1925 (Salt Lake City, UT : Project Gutenberg, 2007)
"Letters to His Friends" by Forbes Robinson is a collection of personal letters and memoirs written in the early 20th century. This work offers insight into the life experiences and thoughts of Robinson, who was a fellow at Christ's College, Cambridge, revealing his reflections on life, education, and spirituality. The letters highlight his relationships with friends and family, discussing themes of personal growth, faith, and the importance of human connection. At the start of this collection, we learn about Forbes Robinson's early life and upbringing, including his family background and schooling. His experiences as a sensitive and introspective child are portrayed, suggesting he was shaped significantly by his father's influence and his love for literature. As he transitions to his time at Rossall School and later, Cambridge, the narrative hints at his deep engagement with theology and literature, alongside a growing network of friendships that he nurtured despite his somewhat reserved nature. The letters he wrote during this time reveal his humor, reflective nature, and strong Christian faith, setting the stage for the profound influence he would later have as a teacher and mentor to his peers. (This is an automatically generated summary.)
Release date is 2007-02-11
Produced by Al Haines
Keywords: Robinson, Forbes, 1867-1904 -- Correspondence; Church of England -- Clergy -- Correspondence; Clergy -- England -- Correspondence